American Association for the Surgery of Trauma Prevention Committee review: Family Justice Centers—a not-so-novel, but unknown gem. Issue 1 (7th June 2021) - Duncan, Thomas K; Stewart, Ronald; Joseph, Kimberly; Kuhls, Deborah A; Dechert, Tracey; Taghavi, Sharven; Bonne, Stephanie; Matsushima, Kazuhide
Abstract : The American College of Surgeons Committee on Trauma requires that trauma centers demonstrate adequate financial support for an injury prevention program as part of the verification process. With the ongoing challenges that arise with important social determinants of health, trauma centers have the important task of navigating a patient through the complex process of obtaining services and tools for success. This summary from the American Association for the Surgery of Trauma Prevention Committee focuses on a model that has been present for several years, but has not been brought to full awareness in the trauma world. It highlights the importance of the Family Justice Center concept that brings a multitude of organizations under one roof, thus eliminating the hurdles encompassed by trauma patients, seeking life-changing resources necessary to mitigate the impact of both community violence exposure and intimate partner/domestic violence. It discusses the potential benefits of a partnership between trauma centers and Family Justice Centers and similar models. Finally, it also raises awareness of important programmatic evaluation research required in the arena of injury prevention targeting a population whose outcomes are difficult to measure.